PERAN KEPOLISAN DALAM MENINDAK PELAKU PENJUALAN MINUMAN KERAS ILEGAL DI KOTA BATAM (STUDI PADA POLRESTA BARELANG) - sari, sinta puspita; Jamba, Padrisan (LPPM Universitas Putera Batam, 2020)
Liquor has a variety of adverse effects that are bad for the community. The efforts of the police in overcoming the distribution of illegal liquor in the city of Batam are through preventive and repressive measures. The role of the police in tackling illegal liquor in the city of Batam was assisted by bhabinkamtibmas and sanctions were only given in the form of fines and confiscations. Based on the theory of legal certainty used by the author that after reviewing it can be seen that the law already exists but many legal certainties are not carried out by members of the police as well as only providing sanctions and not by applicable regulations. This study aims to analyze the empirical juridical or sociology of law to find out more directly the approach by looking at something of the legal reality that already exists in society. The obstacles faced by police members are the absence of legislation relating to alcoholic drinks that do not yet have specific rules in prevention so that the police in handling these matters do not have certainty in providing criminal sanctions to dealers, sellers or buyers that are circulated illegally at Batam city.